2009
DOI: 10.1017/s1751731109990462
|View full text |Cite
|
Sign up to set email alerts
|

Soybean oil and linseed oil supplementation affect profiles of ruminal microorganisms in dairy cows

Abstract: The objective of this study was to evaluate changes in ruminal microorganisms and fermentation parameters due to dietary supplementation of soybean and linseed oil alone or in combination. Four dietary treatments were tested in a Latin square designed experiment using four primiparous rumen-cannulated dairy cows. Treatments were control (C, 60 : 40 forage to concentrate) or C with 4% soybean oil (S), 4% linseed oil (L) or 2% soybean oil plus 2% linseed oil (SL) in a 4 × 4 Latin square with four periods of 21 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
5
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 42 publications
11
107
5
3
Order By: Relevance
“…In this study, ruminal pH and NH 3 -N were not affected by dietary treatments, this partly agrees with the studies by Yang et al (2009) who did not report ruminal pH changes when cows were fed SO and linseed oil, but did observe increases in ruminal NH 3 -N concentration. Benchaar et al (2012) reported no effect on pH, VFA and NH 3 -N when dairy cows were supplemented with linseed oil at 2%, 3% and 4% DM.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this study, ruminal pH and NH 3 -N were not affected by dietary treatments, this partly agrees with the studies by Yang et al (2009) who did not report ruminal pH changes when cows were fed SO and linseed oil, but did observe increases in ruminal NH 3 -N concentration. Benchaar et al (2012) reported no effect on pH, VFA and NH 3 -N when dairy cows were supplemented with linseed oil at 2%, 3% and 4% DM.…”
Section: Discussionsupporting
confidence: 93%
“…Dietary treatments (Table 1) were a basal diet (Control) containing 56% forage and 44% concentrate ratio with no fat supplement, and fat-supplemented diets containing SO (170 g/day per cow = 2.7% DM) and HPO (170 g/day per cow = 2.7% DM). The amounts of oil used were similar to those reported to alter rumen FA in previous studies (Yang et al, 2009;Vargas-Bello-Perez et al, 2015a). The most important FA in dietary oils were as follows: SO contained (g/100 g) 25 of C18:1 cis-9 and 51 of C18:2 cis n-6, whereas HPO contained 47 of C16:0 and 43 of C18:0.…”
Section: Animals and Treatmentssupporting
confidence: 66%
See 3 more Smart Citations